Effects of hydroxyl-functionalization and sub-Tg thermal annealing on high pressure pure- and mixed-gas CO2/CH4 separation by polyimide membranes based on 6FDA and triptycene-containing dianhydrides - Swaidan, Raja; Ghanem, Bader; Litwiller, Eric; Pinnau, I (Journal of membrane science, 2015)
A sub-Tg thermally-annealed (250°C, 24h) ultra-microporous PIM-polyimide bearing a 9,10-diisopropyl-triptycene contortion center and hydroxyl-functionalized diamine (2,2-bis(3-amino-4-hydroxyphenyl)-hexafluoropropane, APAF) exhibited plasticization resistance up to 50bar for a 1:1 CO2/CH4 feed mixture, with a 9-fold higher CO2 permeability (30Barrer) and 2-fold increase in CO2/CH4 permselectivity (~50) over conventional dense cellulose acetate membranes at 10bar CO2 partial pressure. Interestingly, mixed-gas CO2/CH4 permselectivities were 10–20% higher than those evaluated under pure-gas conditions due to reduction of mixed-gas CH4 permeability by co-permeation of CO2. Gas transport, physisorption and fluorescence studies indicated a sieving pore-structure engaged in inter-chain charge transfer complexes (CTCs), similar to that of low-free-volume 6FDA–APAF polyimide. The isosteric heat of adsorption of CO2 as well as CO2/CH4 solubility selectivities varied negligibly upon replacement of OH with CH3 but CTC formation was hindered, CO2 sorption increased, CO2 permeability increased ~3-fold, CO2/CH4 permselectivity dropped to ~30 and CH4 mixed-gas co-permeation increased. These results suggest that hydroxyl-functionalization did not cause preferential polymer-gas interactions but primarily elicited diffusion-dominated changes owing to a tightened microstructure more resistant to CO2-induced dilations. Solution-processable hydroxyl-functionalized PIM-type polyimides provide a new platform of advanced materials that unites the high selectivities of low-free-volume polymers with the high permeabilities of PIM-type materials particularly for natural gas sweetening applications.